TYPES OF FEET IN MACEDONIAN NATIONALITY - Chadikovska, Elizabeta; Matveeva, Niki; Zafirova, Biljana; Bojadzieva Stojanoska, Biljana; Trpkovska, Biljana (Journal of Morphological Sciences; Vol 1 No 2 (2018): JMS, 2018)
The feet are flexible structures of bones, joints, muscles and soft tissues that let us stand upright and perform activities like walking, running or jumping. The feet are divided into three topographic regions: tarsus, metatarsus and phalanges. Muscles, tendons and ligaments run along the surfaces of the feet, allowing the complex movements needed for motion and balance of the human body. There are some positions and differences, compared to the normal feet, which should be compensated in order to move the body properly. Detection of the anatomical differences and abnormalities of the human feet is important because it can cause pain, restrict mobility and disrupt the posture of the human body. Pes-planus or flat footâ€™ is one of the most common conditions observed in adult health practice.  The aim of the study is to determine anatomical differences and to discover possible abnormalities of the human feet. The study consists of plant prints of adults, taken at the Institute of Anatomy, selected by random choice. All of the examinees were above 20 years old. Feet and prints have been observed, analyzed and classified. The most frequent feet were normal ones, pes planus (fallen arch) was detected in very high percentage, at almost half of the male and female examinees, feet with bunion and hammertoe feet were detected in small percentage only among females. Humans rely on the proper functioning of the feet in everyday life, with early detection and accommodation of any present structural problems, treated on time properly; we can move forward in proper and comfort locomotion. Key words: feet, plantograms, locomotion